Ultrasound and Its Combination with Natural Antimicrobials: Effects on Shelf Life and Quality Stability of a Fruit and Vegetable Smoothie - Casco, María de Los Ángeles (2022)
Fruit and vegetable natural beverage market is growing around the world, but their intrinsic characteristics lead to a high microbial and enzymatic activity, showing a short shelf life when not treated. The present work aims to evaluate the effect of ultrasound (US) treatments on the main spoilage factors and some quality indicators of a mixed fruit and vegetable smoothie (F&VS). Likewise, the advantages of combining US with green tea extract (GTE), nisin (Ni), or natamycin (Na) on the shelf life and stability of the F&VS were assessed. Temperature control was needed to avoid high temperatures during treatment and consequent nutrients and organoleptic degradation. Length of treatment lower than 15 min was required to avoid poliphenoloxidase activation. Ultrasound-selected treatment (UST) was of 70% of amplitude during 4 min, since presented the greatest reduction of peroxidase activity (71.6%) and well performance on microbial control. Both UST and UST + GTE treatments extended F&VS microbial shelf life by 1 week, while UST + Na and UST + Ni by at least 2 weeks. UST greatly increased betalain extractability (55–80%). Its combination with GTE significantly increased the TPC and the antioxidant capacity of the product, as well as enhanced betalain stability during storage. Finally, remarkable results on Listeria initial reductions were obtained with UST + Ni (> 4 log) and on Escherichia coli with UST + GTE (1.7 log) when contamination was simulated. Indeed, the potential of US and their combination with natural antimicrobials on quality preservation as well as on shelf life extension and safety assurance of the F&VS was probed with very promising results.